STRATEGIC FACILITIES MANAGEMENT FUNCTIONS FOR PUBLIC PRIVATE PARTNERSHIP (PPP) HEALTHCARE SERVICES IN MALAYSIA - Abdullah Hashim, Hariati; Sapri, Maimunah; Ab. Azis, Shazmin Shareena (PLANNING MALAYSIA, 2019)
There is an increase trend seen in the implementation of public private partnership (PPP) to deliver public infrastructures in Malaysia. In healthcare sectors, particularly hospital, PPP has been adopted by the government as one of the sourcing strategies in providing facilities management (FM) services. In this arrangement, facilities management plays an important role in ensuring the success of partnership. Yet, investigations on strategic facilities management functions are inadequate. Thus, this paper aims at identifying the strategic facilities management functions for PPP healthcare within Malaysian context. Interview sessions were conducted with industries practitioners involved in the implementation of PPP facilities management in Malaysia. Data collected were analysed through content analysis. Responses from the respondents indicated three main categories of strategic FM functions, which are Formulate Strategies, Determine Service Requirement and Communication. The findings provided clear strategic FM functions that are crucial in aligning the FM division with PPP stakeholder’s vision.